The job : work and its future in a time of radical change - Shell, Ellen Ruppel, 1952- (New York : Currency, 2018)
'In a brilliant but sobering work of journalism, Ellen Ruppel Shell takes a hard look at the forces that are reshaping the nature of work in America, overturning the often espoused mythology that retraining workers in software, engineering, and the sciences is the key to job security and career success, and achieving the middle-class dream in the future. In a wide-ranging narrative that takes us from a downsized marketing executive in Massachusetts, to a father of three in Appalachia finding purpose and meaning working in a convenience store chain, to an unemployed autoworker retraining in'advanced manufacturing,' Shell reveals how work is essential to our flourishing and pyschological well-being--and how so many of the avenues to well-paid and meaningful work will be challenged in the years ahead. The future of work is not being faced openly. We live in a world where the rewards of employment are concentrated in the hands of the few. Today, the top 10 percent of wage earners in the U.S. bring home 9 times the income of the other 90 percent, and the top.01 percent earn 184 times as much. The economic gap between the few and the many is so vast, Shell says, that we might as well be members of a different species. Moreover, since the 1970s, real wages for most of us have stagnated, and with it our purchasing power. Half of all Americans earn less than $30,000 a year. And the paths to landing those good-paying jobs that secure our financial future are disappearing in the wake of automation and the rise of AI'--
'In a brilliant but sobering work of journalism, Ellen Ruppel Shell takes a hard look at the forces that are reshaping the nature of work in America, overturning the often espoused mythology that retraining workers in software, engineering, and the sciences is the key to job security and career success, and achieving the middle-class dream in the future. In a wide-ranging narrative that takes us from a downsized marketing executive in Massachusetts, to a father of three in Appalachia finding purpose and meaning working in a convenience store chain, to an unemployed autoworker retraining in'advanced manufacturing,' Shell reveals how work is essential to our flourishing and pyschological well-being--and how so many of the avenues to well-paid and meaningful work will be challenged in the years ahead. The future of work is not being faced openly. We live in a world where the rewards of employment are concentrated in the hands of the few. Today, the top 10 percent of wage earners in the U.S. bring home 9 times the income of the other 90 percent, and the top .01 percent earn 184 times as much. The economic gap between the few and the many is so vast, Shell says, that we might as well be members of a different species. Moreover, since the 1970s, real wages for most of us have stagnated, and with it our purchasing power. Half of all Americans earn less than $30,000 a year. And the paths to landing those good-paying jobs that secure our financial future are disappearing in the wake of automation and the rise of AI'--
Includes bibliographical references (pages 327-385) and index.
Keywords: Work -- United States -- Forecasting; Labor -- United States -- Forecasting